The Role of Collaborative Action Research in Teachers' Professional Development - Castro Garcés, Angela Yicely; Martínez Granada, Liliana (PROFILE: Issues in Teachers' Professional Development, 2016)
Teachers' professional development is a key factor to have more reflective educators capable of working on teams to find solutions to problems that arise in their classrooms. The objective of this study is to analyze the impact that the collaborative planning, implementation, and evaluation of classroom projects, developed through collaborative action research, have in the professional development of in-service and pre-service teachers in a BA in English program. This is a qualitative research study focused on collaborative action research. Data were collected through journals, surveys, and meeting proceedings of collaborative sessions. As a result, it was possible to describe the processes and dynamics generated, as well as the changes perceived, which contributed to the professional development of the participants.
Keywords: Action Research; Diaries; English (Second Language); Faculty Development; Foreign Countries; Inservice Teacher Education; Meetings; Personal Autonomy; Preservice Teacher Education; Qualitative Research; Role; Second Language Instruction; Second Language Learning; Student Attitudes; Surveys; Teacher Attitudes; Teacher Collaboration; Teacher Educators